Transcriptome Profiling During Muscadine Berry Development Reveals the Dynamic of Polyphenols Metabolism - Ismail, Ahmed; Darwish, Ahmed G.; Park, Minkyu; Gajjar, Pranavkumar; Tsolova, Violeta; Soliman, Karam F. A.; El-Sharkawy, Islam (Frontiers in Plant Science, 2022)
Muscadine grapes accumulate higher amounts of bioactive polyphenolics compared to other grape species. To identify the molecular events associated with polyphenolic accumulation that influence antioxidant activity, two contrasting muscadine genotypes (C5 and C6) with varied phenolic/flavonoid content and antioxidant activity were investigated via RNA-sequencing during berry development. The results showed that berry development is concomitant with transcriptome profile changes, which was more pronounced at the véraison (V) stage. Despite that the down-regulation model of gene expression predominated the up-regulation through berry development, the C5 genotype maintained higher expression levels. Comparative transcript profiling allowed the identification of 94 differentially expressed genes with potential relevance in regulating fruit secondary metabolism, including 18 transcription factors and 76 structural genes. The genes underlying the critical enzymes in the modification reactions of polyphenolics biosynthetic pathway, including hydroxylation, methylation, and glycosylation were more pronounced during the immature stages of PrV, V, and PoV in the C5 genotype, resulting in more accumulation of biologically active phenolic/flavonoid derivatives. The results suggested that muscadine grapes, as in bunch grapes (Vitis sp.); possess an analogue mechanism that organizes polyphenolic accumulation; however, the set of TFs and structural genes coordinating the pathway varies between the two species.